2014
DOI: 10.1002/mrm.25458
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional whole‐heart T2 mapping at 3T

Abstract: Free-breathing accurate 3D T2 mapping is feasible and may be applicable in myocardial assessment in lieu of current clinical black blood, T2 -weighted techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(106 citation statements)
references
References 58 publications
(83 reference statements)
6
89
1
Order By: Relevance
“…Three-dimensional (3D) mapping may allow for more complete coverage of the heart and a better characterization of complex regional distribution patterns of disease processes [53, 54, 187]. …”
Section: Future Directionsmentioning
confidence: 99%
“…Three-dimensional (3D) mapping may allow for more complete coverage of the heart and a better characterization of complex regional distribution patterns of disease processes [53, 54, 187]. …”
Section: Future Directionsmentioning
confidence: 99%
“…complete coverage of the heart and better characterization of complex regional distribution of disease processes. [12][13][14][15][16][17][18][19][20][21][22] This has been preliminarily validated in several patient studies. 23,24 However, the relatively long scan time that results from 3D imaging in the presence of cardiac and respiratory motion limits the number of differentially weighted volumes that can be acquired, 12 the measurable range of the relaxation times, 13 and the in-plane resolution.…”
Section: Magnetic Resonance In Medicinementioning
confidence: 94%
“…In van Heeswijk et al (11), a T 2 value range of 35-45 ms was reported across segments. In Ding et al (12), the standard deviation of myocardial T 2 measurements was 3.5-5 ms across the entire myocardium. We FIG.…”
Section: Discussionmentioning
confidence: 94%